2011
DOI: 10.1002/ptr.3576
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl‐ and Butyryl‐cholinesterase Inhibitory Activities of Mansorins and Mansonones

Abstract: Cholinesterase (ChE) inhibitory activities of three coumarins (mansorins A-C) and five naphthoquinones (mansonone C, E, G and H) were evaluated to determine the relationships between the acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitory effects and the core structures of these compounds. Among the tested compounds, mansonone E exhibited the highest ChE inhibitory activities, with IC₅₀ values in the low micromolar levels. In addition to revealing the ChE inhibitory activities of naphthoqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…A study conducted on AChE and BChE inhibitory activity of coumarins and naphtoquinones obtained from Mansonia gagei (Sterculiaceae) proposed a novel class of cholinesterase inhibitor, mansonones or 1,2-naphtoquinones [69]. The level of cholinesterase inhibition observed in this study seemed to correlate to the presence of a fused pyran ring and a substituent at C-6 being present in the molecule.…”
Section: Non-alkaloidal Compounds With Ache Inhibitory Activitymentioning
confidence: 60%
“…A study conducted on AChE and BChE inhibitory activity of coumarins and naphtoquinones obtained from Mansonia gagei (Sterculiaceae) proposed a novel class of cholinesterase inhibitor, mansonones or 1,2-naphtoquinones [69]. The level of cholinesterase inhibition observed in this study seemed to correlate to the presence of a fused pyran ring and a substituent at C-6 being present in the molecule.…”
Section: Non-alkaloidal Compounds With Ache Inhibitory Activitymentioning
confidence: 60%
“…The presence of a fused pyran ring favours anti‐ChE activity: masonones E and H, having this feature, are more active than mansonones C and G, which do not present this characteristic. In contrast, the presence of a hydroxyl group at C6 induces a decrease of the inhibitory activity: mansonones C and E are more active than mansonones G and H, respectively …”
Section: Quinonesmentioning
confidence: 94%
“…Mimulone 91.5 Human erythrocytes [56] 20.6 Equine serum [56] Naringenin 2045 Human erythrocytes [56] 1494 Equine serum [56] Pomiferin 96 Electric eel [57] N.F. Horse serum [57] Quercetin 353.9 Pacific electric ray [58] 420.8 Horse serum [58] Rutin 28.2 Electric eel [59] 44.6 Horse serum [59] Tamarixetin 22.3 N.M. [54] 160.6 N.M. [54] Quinones Mansonone E 23.5 Electric eel [60] 62.4 Horse serum [60] Sargaquinoic acid 23.3 N.M. [61] 0.026 N.M. [61] Stilbenes (+)-a-Viniferin 2.0 N.M. [62] N.F. Gnetol N.F.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Among quinone-related compounds, it has been reported that the IC 50 values of sargaquinoic acid and mansonones E are 23.3 and 23.5 μM, respectively [12]. In our experimental setting, the anti-AChE activity of EchA was better than other quinone-related compounds, sargaquinoic acid and mansonones E [30]. However, direct comparison of compounds on anti-AChE activity needs caution, since the inhibitory concentrations of tested compounds are dependent on incubation time, reaction conditions, source of enzymes and assaying method [8].…”
Section: Resultsmentioning
confidence: 68%